Field of dreams - Robinson, Phil Alden; Gordon, Lawrence; Gordon, Charles; Kinsella, W.P (Universal City Studio, 1989)
When Ray Kinsella hears a voice in his field and has a vision of a baseball field, he builds a baseball diamond in his cornfield. Soon players from the infamous 1919 Chicago "Black" Sox, led by Shoeless Joe Jackson, return to play in his field.